Enhanced endogenous oxytocin signaling in the brain modulates neural responses to social misalignment and promotes conformity in humans: A multi-locus genetic profile approach. (October 2022) - Lee, Minwoo; Lori, Adriana; Langford, Nicole A.; Rilling, James K.
Abstract: The neuropeptide oxytocin (OT) is known to promote social conformity. However, the specific neurocognitive mechanisms underlying OT-induced conformity remain unclear. We aimed to address this gap by examining how genetic variation in the oxytocin receptor gene ( OXTR ) is linked with behavioral conformity and its underlying neural systems. Specifically, we utilized the genotype-tissue expression database (GTEx) to create a novel multi-locus genetic profile score (MPS) that reflects the level of OXTR expression in the human brain. A total of 194 participants (Neuroimaging N = 50, Behavioral N = 144) performed a novel conformity task in which they viewed a series of word pairs depicting various moral values and virtues widely recognized in the United States. In each trial, participants indicated the relative importance of these words and subsequently learned about the majority opinion. Participants later rated the same word pairs a second time. Changes in participants' ratings between the first and second sessions were measured and analyzed with respect to social feedback, blood oxygen level-dependent (BOLD) functional magnetic resonance imaging (fMRI) signals, and OXTR MPS. We found that participants adjusted their ratings in accordance with the majority opinions. Social misalignment between self and others activated brain areas such as the striatum and the posterior medial frontal cortex (pMFC). However, unlike most findings from previous studies, activation in the pMFC during the inconsistent social feedback negatively, rather than positively, predicted behavioral conformity. Notably, those with higher OXTR MPS had reduced pMFC activation in the face of social misalignment, which led to greater conformity. Our findings suggest that OT may promote conformity by dampening the conflict-related signals in the pMFC. They also show that OXTR MPS may be useful for studying the effect of genes on highly complex human social traits, such as conformity. Highlights: Participants exhibited behavioral conformity in the domain of moral values and virtues. Social misalignment between self vs. others activated the caudate nucleus and posterior medial frontal cortex (pMFC). Increased pMFC activation negatively predicted behavioral conformity. OXTR multi-locus genetic profile scores negatively predicted the pMFC activation in response to social misalignment. Decreased pMFC activation mediated the association between OXTR MPS and increased behavioral conformity.